One-Dimensional Mappings - Leonel, Edson Denis [UNESP] (My University, 2021)
This chapter is dedicated to the concept of discrete mappings. We show that applications of the discrete mappings come from the idea of surface of section also called as Poincaré section. We briefly discuss how to obtain the fixed points and classify their stability particularly addressed to the logistic map.